2017
DOI: 10.1002/btpr.2588
|View full text |Cite
|
Sign up to set email alerts
|

Sulfanilic acid‐modified chitosan mini‐spheres and their application for lysozyme purification from egg white

Abstract: A cation exchange matrix with zwitterionic and multimodal properties was synthesized by a simple reaction sequence coupling sulfanilic acid to a chitosan based support. The novel chromatographic matrix was physico-chemically characterized by ss-NMR and ζ potential, and its chromatographic performance was evaluated for lysozyme purification from diluted egg white. The maximum adsorption capacity, calculated according to Langmuir adsorption isotherm, was 50.07 ± 1.47 mg g while the dissociation constant was 0.07… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
(82 reference statements)
0
13
0
Order By: Relevance
“…Chitosan mini-spheres (1.32 ± 0.14 mm diameter) were obtained according to the procedure described in previous studies (Baieli et al, 2014b;Hirsch et al, 2018a). Briefly, a chitosan solution was prepared by dissolving 2% of low viscosity chitosan powder (acetylation degree 41%) in 2% acetic acid (Kasaai, Arul, & Charlet, 2000).…”
Section: Matrix Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…Chitosan mini-spheres (1.32 ± 0.14 mm diameter) were obtained according to the procedure described in previous studies (Baieli et al, 2014b;Hirsch et al, 2018a). Briefly, a chitosan solution was prepared by dissolving 2% of low viscosity chitosan powder (acetylation degree 41%) in 2% acetic acid (Kasaai, Arul, & Charlet, 2000).…”
Section: Matrix Synthesismentioning
confidence: 99%
“…The ζ potential study was performed as previously reported (Hirsch et al, 2018a). Briefly, the matrices were first disrupted mechanically (100 mg 10 mL -1 distilled water) with a spatula and then kept under magnetic stirring for 48 h to obtain a homogeneous microparticle suspension.…”
Section: Zeta Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrogels based on bio-composites polymers have been intensively studied for protein purification [5]. Compared with the widely studied hydrogels based J o u r n a l P r e -p r o o f on synthetic polymers, such as acrylic acid, acrylamide and poly(ethylene glycol), the hydrogels based on biopolymers, such as alginate [6], carboxymethyl cellulose [7], silk [8], chitosan [9]and chitin derived polymers [10], have recently captured researchers interest due to their biocompatibility, nontoxicity and biodegradability.…”
Section: Introductionmentioning
confidence: 99%